Differences Between Teachers in Regular Classes and Classes with Disabilities in the Practice of Meta-Cognitive Skills in the Teaching Process - Alyousef, Hayfaa; Aldoukhi, Fawzi; Aldherwa, Mubarak (Jordan Journal of Educational Sciences, 2017)
The the purpose of the study is to identify to what extent teachers in regular and disabilities classes practice meta-cognitive skills, with the impact of some demographic variables such as gender, nationality, and learning stage. A descriptive comparative approach was used. The sample of the study consisted of (786) teachers: (654) teachers of regular classes and (132) teachers of disabilities. A questionnaire of three dimensions of planning, monitoring and evaluation was applied. A lower practice of meta-cognitive skills in both teachers of regular and disabilities classes was found in all dimensions. Also, statistically significant differences in the evaluation dimension between male and female teachers of regular classes in favor of males were found, yet no statistically significant differences between the groups in planning and monitoring dimensions appeared. In contrast, the result of disabilities schools showed that female teachers practiced meta-cognitive skills over the three dimensions (planning, monitoring, evaluation) more than their male peers